Solar panels in pavements: Advantages, limitations, and future development - Manić Nazim U.; Ikić Selver H.; Maslak Emir Š.; Manić Džemil N. (Tehnika)
The use of solar panels in road pavements represents an innovative approach to integrating renewable energy sources, specifically solar energy, into everyday infrastructure. This paper explores the key aspects of this technology, including its advantages, disadvantages, and potential for future development. The benefits include improving energy efficiency and reducing dependence on fossil fuels, as well as the ability to generate electricity directly at the point of use, which can contribute to lowering energy costs. Solar panels in road pavements can also help reduce air pollution and improve environmental standards in urban areas. The disadvantages involve challenges such as high installation and maintenance costs, the need for regular cleaning of the panels due to dirt and debris accumulation, and limited efficiency under poor weather conditions or at night. Additionally, there is a need for infrastructure adaptation and possible aesthetic or structural obstacles in implementation. The future of applying solar panels in road pavements looks promising, with opportunities for technology advancement, cost reduction, and increased energy efficiency. This paper provides a comprehensive overview of the current application of solar panels in road pavements, highlights existing challenges, and offers recommendations for future research and development in this exciting field of renewable energy technology.